AllergoOncology: Danger signals in allergology and oncology: A European Academy of Allergy and Clinical Immunology (EAACI) Position Paper. Issue 9 (14th March 2022) - Bergmann, Christoph; Poli, Aurélie; Agache, Ioana; Bianchini, Rodolfo; Bax, Heather J.; Castells, Mariana; Crescioli, Silvia; Dombrowicz, David; Ferastraoaru, Denisa; Fiebiger, Edda; Gould, Hannah J.; Hartmann, Karin; et al.
Abstract: The immune system interacts with many nominal 'danger' signals, endogenous danger‐associated (DAMP), exogenous pathogen (PAMP) and allergen (AAMP)‐associated molecular patterns. The immune context under which these are received can promote or prevent immune activating or inflammatory mechanisms and may orchestrate diverse immune responses in allergy and cancer. Each can act either by favouring a respective pathology or by supporting the immune response to confer protective effects, depending on acuity or chronicity. In this Position Paper under the collective term danger signals or DAMPs, PAMPs and AAMPs, we consider their diverse roles in allergy and cancer and the connection between these in AllergoOncology. We focus on their interactions with different immune cells of the innate and adaptive immune system and how these promote immune responses with juxtaposing clinical outcomes in allergy and cancer. While danger signals present potential targets to overcome inflammatory responses in allergy, these may be reconsidered in relation to a history of allergy, chronic inflammation and autoimmunity linked to the risk of developing cancer, and with regard to clinical responses to anti‐cancer immune and targeted therapies. Cross‐disciplinary insights in AllergoOncology derived from dissecting clinical phenotypes of common danger signal pathways may improve allergy and cancer clinical outcomes. Abstract :